PICO-HYDRO POWER GENERATION USING A SMALL WATER TURBINE FOR THE TERTIARY CANAL APPLICATION (UIR PRESS, 2025)
This study aimed to develop a pico-hydro water turbine capable of generating electricity from a tertiary irrigation canal, harnessing water flow as a sustainable power source for rural communities. Various blade types and water barrier heights were tested, with data analysed using a factorial arrangement in a Completely Randomised Design. Results showed that the water barrier height significantly influenced power output, with a maximum theoretical power of 613 W at a barrier height of 0.4 m. The turbine achieved a rotational speed of 43 rpm and generated 63 W of actual power, corresponding to an efficiency of 13% at a barrier height of 0.3 m. Financial analysis indicated that the system could reduce a household’s annual electricity bill by 11%, confirming its technical feasibility and economic viability as a small-scale renewable energy solution.